Quantitative live cell imaging reveals influenza virus manipulation of Rab11A transport through reduced dynein association - Amar R. Bhagwat (Nature Portfolio, 2020)
Here, using high spatiotemporal resolution light-sheet and fluorescence microscopy, the authors investigate the role of cytoskeletal components on the intracellular transport of Rab11A and influenza virus (IAV) vRNP), and show a preference for Rab11A movement along microtubules that is not essential for IAV vRNP transport.